The development of forced disappearance and its special elements of configuration in Colombia - Sandoval Mesa, Jaime (University Santo Tomás, Bogotá, 2016)
The crime of enforced disappearance is one of the most serious crimes against the international community, so much so it is considered a crime against humanity under the Rome Statute of 1998, for the establishment of the International Criminal Court. However the importance of the offence in question, only since the year 2000 notes his characterization in Colombia, despite the fact that reported a history of the analysed conduct, since the end of the 1970s. However, advances in the domestic law are significant and are the current prospect of prosecution of international crimes in Colombia, with the consequences that this represents to the international community.